The Relationship Between Place and Youth Volunteerism: Building Bonds and Breaking Barriers - Pearce, Sean (Université d'Ottawa / University of Ottawa, 2017)
Volunteerism is a popular form of community engagement among youth and can involve helping organizations, such as nonprofits, as well as directly assisting neighbours or friends through informal types of helping. A large body of research has examined the different ways in which economic, social, and cultural resources impact on volunteerism. Fewer studies have considered the influence of place characteristics. This dissertation comprises three studies. The first study used secondary data to explore the moderating effects of urban/rural place of residence and certain resources (e.g., religiosity, work status) on youths’ volunteer propensity and intensity. Results revealed significant urban/rural interactions. For example, belonging to youth groups (versus not) was particularly a strong lever for rural youth volunteerism, while higher religious attendance frequency was associated with greater volunteer intensities for urban youth. The second study used a mixed methods approach to investigate urban/rural differences in motivations for and barriers to volunteering, and skills acquired. Financial costs were associated with nonvolunteer status for rural youth, while urban nonvolunteers reported lacking interest. During the interviews, youth described reasons for volunteering, challenges to volunteering, and strategies to improve volunteerism. These discussions differed by urban/rural residence. Rural youth reported more contextual barriers, whereas urban youth questioned the significance of their impact. Rural youth discussed volunteering more as a general learning experience, whereas urban youth tended to mention specific skills they acquired (e.g., technical, interpersonal). In the third study, the relationships between perceptions of the neighbourhood environment (e.g., cohesion, amenities) and volunteer outcomes were explored. Results revealed that neighbourhood cohesion was particularly important to informal volunteering. Further, different clusters emerged based on volunteer type (informal/formal) and level of intensity. The findings from this dissertation suggest that understanding youth volunteerism within a socio-ecological perspective can widen our understanding of the volunteer process, including antecedents, challenges, experiences, and outcomes. This research may have practical implications for nonprofit organizations. For example, methods of outreach should consider how the environment impacts on volunteerism when trying to recruit young volunteers. Finally, the literature on youth volunteerism may benefit by adopting a holistic approach to volunteerism that considers the different ways in which place characteristics, rather than only individual-level factors, influence youth community engagement.
Keywords: Volunteering; Youth; Rural; Urban; Informal volunteering; Socio-ecological